2012
DOI: 10.1590/s0102-09352012000500042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da infecção por Toxoplasma gondii em galinhas criadas extensivamente em Rio Bonito, Rio de Janeiro

Abstract: A toxoplasmose é uma zoonose que acomete mamíferos e aves. As galinhas de criações extensivas são hospedeiros indicadores da contaminação ambiental por oocistos de Toxoplasma gondii, pois se alimentam no solo, que pode estar contaminado com oocistos esporulados, infectando-se e desenvolvendo cistos teciduais (Dubey, 2010). Nas criações extensivas, as galinhas possuem maior possibilidade de adquirir infecção por T. gondii e de transmitir esse protozoário ao homem pelo consumo e manipulação de sua carne, quando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In Brazil, studies have showed high prevalence of T. gondii infection in poultry in the southern region (GARCIA et al, 2000) and southeastern region (CASARTELLI-ALVES et al, 2012), thus suggesting that high environmental contamination is present, with a high risk of human and animal infection. However, few studies on occurrences of T. gondii infection in free-range chickens have been conducted, especially in the northeastern region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies have showed high prevalence of T. gondii infection in poultry in the southern region (GARCIA et al, 2000) and southeastern region (CASARTELLI-ALVES et al, 2012), thus suggesting that high environmental contamination is present, with a high risk of human and animal infection. However, few studies on occurrences of T. gondii infection in free-range chickens have been conducted, especially in the northeastern region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Free-range chickens are good indicators of environmental contamination since they feed from the ground, exposing them to infection with T. gondii oocysts (Dubey et al, 2012). Another fact of epidemiological importance is that raw or undercooked chicken meat is an important source of infection for humans and other animals when it is consumed or handled without good hygiene (Casartelli-Alves et al, 2012;Dubey et al, 2012;Hill and Dubey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Um aspecto importante a ser destacado é a presença de aves negativas na sorologia e positivas na PCR, mostrando que mesmo galinhas caipiras soronegativas podem ter cistos em suas vísceras e musculatura, servindo de fonte de infecção para animais ou pessoas que consumirem as mesmas. Este fato se torna relevante quando considera-se que a principal forma usada para detectar animais positivos para T. gondii é pelo uso de exames sorológicos (TENTER, 2009;DUBEY, 2010;CASARTELLI-ALVES et al, 2012).…”
Section: Methodsunclassified